Streptococcus Intermedius Lung Abscess in a 17-year-old Male (Translation: The University of Toledo Journal of Medical Sciences, 2019)
Streptococcus intermedius lung abscess and empyema is a chronic infectious process associated with a high morbidity and mortality.  It is typically seen in adults, and is considered a rare disease process in the pediatric population.  Our case describes a 17 year old male presenting with 3 months of cough associated with later development of chest and back pain.  He was later found to have a severe empyema secondary to Streptococcus intermedius.  This case underlines a rare diagnosis in the pediatric population, as well as a association with smoking and vaping.
Keywords: marijuana; vapingsmoking; intermedius; empyema